Establishing fungal entomopathogens as endophytes: towards endophytic biological control - Parsa, S; Ortíz, V.; Vega, Fernando E. (MyJove Corporation, 2013)
Beauveria bassiana is a fungal entomopathogen with the ability to colonize plants endophytically. As an endophyte, B. bassiana may play a role in protecting plants from herbivory and disease. This protocol demonstrates two inoculation methods to establish B. bassiana endophytically in the common bean (Phaseolus vulgaris), in preparation for subsequent evaluations of endophytic biological control. Plants are grown from surface-sterilized seeds for two weeks before receiving a B. bassiana treatment of 108 conidia/ml (or water) applied either as a foliar spray or a soil drench. Two weeks later, the plants are harvested and their leaves, stems and roots are sampled to evaluate endophytic fungal colonization. For this, samples are individually surface sterilized, cut into multiple sections, and incubated in potato dextrose agar media for 20 days. The media is inspected every 2-3 days to observe fungal growth associated with plant sections and record the occurrence of B. bassiana to estimate the extent of its endophytic colonization. Analyses of inoculation success compare the occurrence of B. bassiana within a given plant part (i.e. leaves, stems or roots) across treatments and controls. In addition to the inoculation method, the specific outcome of the experiment may depend on the target crop species or variety, the fungal entomopathogen species strain or isolate used, and the plant's growing conditions.